2021
DOI: 10.3389/fpsyg.2021.625555
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Language Skills and Comprehension Monitoring to Chinese Reading Comprehension: A Longitudinal Investigation

Abstract: This study examined how vocabulary, syntactic knowledge, and orthographic knowledge are related to comprehension monitoring and whether comprehension monitoring mediates the relations between these language skills and reading comprehension. Eighty-nine Chinese children were assessed on their vocabulary, syntactic knowledge, orthographic knowledge, and comprehension monitoring in Grade 1. Their reading comprehension skills were assessed in Grade 1 and Grade 3. Results showed that in Grade 1, comprehension monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
(188 reference statements)
2
3
0
Order By: Relevance
“…The hierarchical regression analyses results showed that syntactic awareness uniquely contributed to L2 Chinese passage-level reading comprehension by Chinese. Those results were in line with previous work examining the associations of syntactic awareness and reading comprehension in alphabetic languages (e.g., Muter et al, 2004;Nation and Snowling, 2004) and in L1 Chinese (e.g., Yeung et al, 2013;Tong et al, 2014;Zhao et al, 2021b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The hierarchical regression analyses results showed that syntactic awareness uniquely contributed to L2 Chinese passage-level reading comprehension by Chinese. Those results were in line with previous work examining the associations of syntactic awareness and reading comprehension in alphabetic languages (e.g., Muter et al, 2004;Nation and Snowling, 2004) and in L1 Chinese (e.g., Yeung et al, 2013;Tong et al, 2014;Zhao et al, 2021b).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, recent evidence in reading in Chinese has also shown that syntactic awareness plays a role in reading in Chinese among native children (e.g., Yeung et al, 2013;Tong et al, 2014;Zhao et al, 2021b). Yeung et al (2013) constructed a model of reading comprehension among 248 Chinese elementary school fourth grade children.…”
Section: Introductionmentioning
confidence: 98%
“…In line with prior research on the effectiveness of metacognitive language stimulation programs [64,65], strategies for practicing analyzing texts, searching for keywords, and paraphrasing sentences and paragraphs of the educational text were included in the intervention, as they were expected to lead to improved reading comprehension, and may have been central to children's improvement in sentence completion. These results are in line with the research of Zhao and Guo (2021) [66], that showed the contribution of syntactic knowledge to reading comprehension.…”
Section: Language Abilities Related To Reading Comprehensionsupporting
confidence: 92%
“…In this field of study, over the last few years, research about reading comprehension in monolingual and bilingual populations has increased considerably (Choi et al, 2017;Spencer and Wagner, 2017;D'Angelo et al, 2020;Zhang et al, 2020;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%